2020
DOI: 10.4102/phcfm.v12i1.2212
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of malaria rapid diagnostic test (mRDT CareStatTM) compared with microscopy amongst under five children attending a primary care clinic in southern Nigeria

Abstract: Background: Malaria diagnosis using microscopy is currently the gold standard. However, malaria rapid diagnostic tests (mRDTs) were developed to simplify the diagnosis in regions without access to functional microscopy.Aim: The objective of this study was to compare the diagnostic accuracy of mRDT CareStatTM with microscopy.Setting: This study was conducted in the paediatric primary care clinic of the Federal Medical Centre, Asaba, Nigeria.Methods: A cross-sectional study for diagnostic accuracy was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…The specificity of the RDT was lower than that reported by another study in southern Nigeria. This difference may be due to the high false positive rate of the RDT compared with the PCR [2]. The predictive values obtained in this study, apart from the LM PPVs, were in line with another study [37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The specificity of the RDT was lower than that reported by another study in southern Nigeria. This difference may be due to the high false positive rate of the RDT compared with the PCR [2]. The predictive values obtained in this study, apart from the LM PPVs, were in line with another study [37].…”
Section: Discussionsupporting
confidence: 87%
“…It is a pervasive parasitic disease in tropical and subtropical regions. It is mostly prevalent in Sub-Saharan Africa, Asia and Latin America [1,2]. The Sub-Sahara African region accounts for the greatest burden in terms of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…30 Another study in children showed comparable sensitivity in parasite detection although the correlation between the 2 methods of diagnosis was better with high parasite density. 31 Furthermore, the "plus system" of parasitology report is an old method, which is simple but has less accuracy for establishing parasite density in the blood film. 30,32 It is therefore recommended that the actual parasite count per microliter (µ/L) be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T3 was developed to improve surveillance for malaria cases and deaths and help Ministries of Health to determine which areas or population groups are most affected and help target resources where they are most needed. However, the use of malaria diagnostics remains to be limited, and opinions are divided on its utility [16,17].…”
Section: Discussionmentioning
confidence: 99%